Tailoring Practically Accessible Polymer/Inorganic Composite Electrolytes for All-Solid-State Lithium Metal Batteries: A Review - Liang, Hongmei; Wang, Li; Wang, Aiping; Song, Youzhi; Wu, Yanzhou; Yang, Yang; He, Xiangming (Nano-Micro Letters, 2023)
Solid-state electrolytes (SSEs) are widely considered the essential components for upcoming rechargeable lithium-ion batteries owing to the potential for great safety and energy density. Among them, polymer solid-state electrolytes (PSEs) are competitive candidates for replacing commercial liquid electrolytes due to their flexibility, shape versatility and easy machinability. Despite the rapid development of PSEs, their practical application still faces obstacles including poor ionic conductivity, narrow electrochemical stable window and inferior mechanical strength. Polymer/inorganic composite electrolytes (PIEs) formed by adding ceramic fillers in PSEs merge the benefits of PSEs and inorganic solid-state electrolytes (ISEs), exhibiting appreciable comprehensive properties due to the abundant interfaces with unique characteristics. Some PIEs are highly compatible with high-voltage cathode and lithium metal anode, which offer desirable access to obtaining lithium metal batteries with high energy density. This review elucidates the current issues and recent advances in PIEs. The performance of PIEs was remarkably influenced by the characteristics of the fillers including type, content, morphology, arrangement and surface groups. We focus on the molecular interaction between different components in the composite environment for designing high-performance PIEs. Finally, the obstacles and opportunities for creating high-performance PIEs are outlined. This review aims to provide some theoretical guidance and direction for the development of PIEs. Highlights: 1 The current issues and recent advances in polymer/inorganic composite electrolytes are reviewed. 2 The molecular interaction between different components in the composite environment is highlighted for designing high-performance polymer/inorganic composite electrolytes. 3 Inorganic filler properties that affect polymer/inorganic composite electrolyte performance are pointed out. 4 Future research directions for polymer/inorganic composite electrolytes compatible with high-voltage lithium metal batteries are outlined.